ANALISIS STRATEGI PEMASARAN METODE SWOT DALAM UPAYA MENINGKATKAN PENJUALAN PADA PT. AJ CENTRAL ASIA RAYA CABANG SURABAYA - Mutakin, Muhammad Khakul; Safa’atillah, Nurus (Media Mahardhika, 2018)
Marketing strategy is a suggestion to communicate the company's goals with the direction to be taken to achieve the goal. The use of SWOT analysis is one tool used to determine the advantages and disadvantages of a company. So is the consumer's appetite for unit link products. Unit link products play an important role for everyone in order to prevent and transfer losses that will occur. The method used in this study is qualitative with qualitative descriptive approach, the type of case study research on the object of research using observation methods, interviews and documentation. While the method of data analysis using SWOT analysis techniques (Strengths, Weaknesses, Opportunities, Threats). Based on the weight diagram and rating of each SWOT matrix element can be known that the position of the company or agency PT. AJ Central Asia Raya is currently in the first quadrant is a very favorable situation. Company PT. AJ Centtral Asia Raya Has Internal Coordinates: (Total Score Strength - Total Score Weakness) = 1.97 - 1.35 = 0.62. External Coordinate: (1.79 - 1.40 = 0.39, so the coordinate point lies at (0.62; 0.39), so it can take advantage of the opportunities that exist. The Marketing Strategy used by PT. AJ Central Asia Raya is Aggressive Strategy.